IMPLEMENTASI PROGRAM ALOKASI DANA DESA (ADD) DI DESA DODA KECAMATAN LORE TENGAH KABUPATEN POSO - Woiya, Krisnawati (Katalogis, 2018)
This study aimed to determine the implementation of Village Fund Allocation (Alokasi Dana Desa - ADD) Policy in Doda Village Central Lore District Poso Regency. The method used in this study was qualitative method in which the main instrument in this study was the researcher itself. The data used were primary and secondary data relating to the empirical situation and condition of the policy implementation. This study used the theory of Edward III. The results showed that the implementation of Village Fund Allocation Policy in Doda Village Central Lore District Poso Regency had not been running optimally because it was showed that from the 4 (four) aspects studied, there were two (2) aspects that were not running well, namely the communication aspect, (lack of socialization) and the resources aspect (inadequate human resources and infrastructures), while the two (2) aspects that had been running well enough were the aspect of implementers disposition (enough to support the policy implementation) and the aspect of the bureaucratic structure (where all the implementers had been working in accordance with the duties and functions of each).